Teachers’ perceptions on the development and implementation of History 2166 syllabus reform in Zimbabwe - Sengai, Walter; Mokhele, Matseliso L. (Penerbit Universiti Kebangsaan Malaysia, 2020)
In 1990, Zimbabwe underwent its first major post-colonial syllabus reform in the teaching of History at secondary school level. Scholars who have studied this reform usually overlook teachers’ perceptions when explaining its development and implementation. This qualitative study explores History teachers’ perceptions on their participation in the planning and implementation of the History 2166 syllabus reform. Using qualitative phenomenological design methodology, the researchers listened to the voice of the voiceless, as teachers expressed their perspectives, views, understanding, and interpretations on the syllabus reform during semi-structured interviews with five purposively sampled History teachers drawn from five different schools within the Glen View/Mufakose district in Harare province. The interviews were further transcribed, coded and categorised into meaningful themes. All the participants signed consent forms to demonstrate their willingness to participate in the study. This study appreciates that teachers are the chalk-face implementers of syllabus reforms in any given context of change and their views matter. The key finding was that the ‘top-down’ approach used during this syllabus reform proved disastrous, ultimately producing a teacher-proof syllabus that deskilled and disempowered teachers thereby leading to tissue-rejection and its ultimate failure to effectively address key expectations. The research concludes that previous explanations on the success and/or failure of curriculum reforms were rather incomplete for they sidestepped teachers’ perceptions in explaining the development and implementation of the reforms in the first place.